Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3139/146.110888
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of electrospun fibrous scaffold produced from Indian eri silk fibroin

Abstract: A scaffold, synthesized from bio-degradable polymers and Bombyxmori silk fibroin in the form of films and fibrous assemblies, has been used as the bio-material for in-vivo applications. In the present work, the scaffold was prepared from the fibroin of Indian eri silk via the electrospinning method. The diameter of the fibre produced was in the range of 300 to 900 nm. The scaffold was subjected to ethanol treatment to improve its dimensional stability, as there was the problem of curling and shrinking when it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The degummed fibers exhibited peaks centered at 1654 cm À1 , 1535 cm À1 , and 1240 cm À1 attributed to the typical dominant beta sheet along with turn and random coil conformation (Fig. 1C-I) [37][38][39][40][41]. When comparing the degummed fiber (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The degummed fibers exhibited peaks centered at 1654 cm À1 , 1535 cm À1 , and 1240 cm À1 attributed to the typical dominant beta sheet along with turn and random coil conformation (Fig. 1C-I) [37][38][39][40][41]. When comparing the degummed fiber (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In another research work, the semi-alkali-treated silk fibres were incorporated as a reinforcing agent, while a mixture of 20% maleic anhydride-grafted polypropylene (MAPP) and time commercial grade polypropylene (PP) was used as a matrix element [17]. Andiyappan et al found that eri silk is suitable for wound-dressing applications due to its biochemical composition and lower sericin content, which enhances cell attachment behaviour [18]. Similarly, Chiriac et al stated that silk fibre characteristics are interesting for medical applications such as the induction of no or only a weak immune response, low bacterial adherence, and inherent biodegradability, among other desirable attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of silk fibroin nanofibers was studied using an X-ray diffractometer with a LynxEye detector [67], a CuKα radiation source (wavelength λ = 0.1541 nm) operating at 40kV and 40 mA over diffraction angles measured from 2θ = 0-40 °, and an X'celerator counter [49], [69] at a scanning rate of 0.015 °/s [67], 0.040 °/s [49], 0.048 °/s [70]. These parameters serve to obtain an X-ray diffractogram [71].The crystallinity of the silk fibroin nanofibers and the variation in the percentage of -sheet content corresponding to the crystal structure due to enzymatic degradation were determined [49].…”
Section: Crystalline Structure -X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…In addition, these peaks indicate the coexistence of crystalline and amorphous structures in the electrospun of silk fibroin nanofibers although they were treated with methanol [69]. The estimated percentage of crystallinity of the pure silk fibroin membrane was 22.24 % [47]; its increase (to 35.54 %) is attributed to methanol [47], [66], [70], [72].…”
Section: Crystalline Structure -X-ray Diffraction (Xrd)mentioning
confidence: 99%